Antiarrhythmic drugs. Issue 5 (May 2021) - Jones, Benjamin; Burnand, Cally
Abstract: Around 3.7 million people worldwide die each year from cardiac arrhythmias. Despite advances in catheter ablation therapies and implantable devices, there have been few advances in pharmacological therapy. Advances in the understanding of channel subtypes has led to the proposed modification of the Vaughan Williams classification system. However, each drug has a unique pharmacokinetic profile meaning that often the class of a drug bears little clinical relevance. Many drugs also have sites of action outside of their class which may account for the generation of proarrhythmias. The advances in understanding of specific ion channel subtypes may provide the opportunity for target specific drugs with improved safety profiles.